Nivolumab plus rucaparib for metastatic castration-resistant prostate cancer: results from the phase 2 CheckMate 9KD trial. Issue 8 (17th August 2022) - Fizazi, Karim; Retz, Margitta; Petrylak, Daniel P; Goh, Jeffrey C; Perez-Gracia, Jose; Lacombe, Louis; Zschäbitz, Stefanie; Burotto, Mauricio; Mahammedi, Hakim; Gravis, Gwenaelle; Bastos, Diogo Assed; McCune, Steven L; et al.
Abstract : Background: CheckMate 9KD (NCT03338790 ) is a non-randomized, multicohort, phase 2 trial of nivolumab plus other anticancer treatments for metastatic castration-resistant prostate cancer (mCRPC). We report results from cohorts A1 and A2 of CheckMate 9KD, specifically evaluating nivolumab plus rucaparib. Methods: CheckMate 9KD enrolled adult patients with histologically confirmed mCRPC, ongoing androgen deprivation therapy, and an Eastern Cooperative Oncology Group performance status of 0–1. Cohort A1 included patients with postchemotherapy mCRPC (1–2 prior taxane-based regimens) and ≤2 prior novel hormonal therapies (eg, abiraterone, enzalutamide, apalutamide); cohort A2 included patients with chemotherapy-naïve mCRPC and prior novel hormonal therapy. Patients received nivolumab 480 mg every 4 weeks plus rucaparib 600 mg two times per day (nivolumab dosing ≤2 years). Coprimary endpoints were objective response rate (ORR) per Prostate Cancer Clinical Trials Working Group 3 and prostate-specific antigen response rate (PSA50 -RR; ≥50% PSA reduction) in all-treated patients and patients with homologous recombination deficiency (HRD)-positive tumors, determined before enrollment. Secondary endpoints included radiographic progression-free survival (rPFS), overall survival (OS), and safety. Results: Outcomes (95% CI) among all-treated, HRD-positive, and BRCA1/2 -positive populations for cohort A1 were confirmed ORR: 10.3% (3.9–21.2) (n=58), 17.2% (5.8–35.8) (n=29), and 33.3% (7.5–70.1) (n=9); confirmed PSA50 -RR: 11.9% (5.9–20.8) (n=84), 18.2% (8.2–32.7) (n=44), and 41.7% (15.2–72.3) (n=12); median rPFS: 4.9 (3.7–5.7) (n=88), 5.8 (3.7–8.4) (n=45), and 5.6 (2.8–15.7) (n=12) months; and median OS: 13.9 (10.4–15.8) (n=88), 15.4 (11.4–18.2) (n=45), and 15.2 (3.0–not estimable) (n=12) months. For cohort A2 they were confirmed ORR: 15.4% (5.9–30.5) (n=39), 25.0% (8.7–49.1) (n=20), and 33.3% (7.5–70.1) (n=9); confirmed PSA50 -RR: 27.3% (17.0–39.6) (n=66), 41.9 (24.5–60.9) (n=31), and 84.6% (54.6–98.1) (n=13); median rPFS: 8.1 (5.6–10.9) (n=71), 10.9 (6.7–12.0) (n=34), and 10.9 (5.6–12.0) (n=15) months; and median OS: 20.2 (14.1–22.8) (n=71), 22.7 (14.1–not estimable) (n=34), and 20.2 (11.1–not estimable) (n=15) months. In cohorts A1 and A2, respectively, the most common any-grade and grade 3–4 treatment-related adverse events (TRAEs) were nausea (40.9% and 40.8%) and anemia (20.5% and 14.1%). Discontinuation rates due to TRAEs were 27.3% and 23.9%, respectively. Conclusions: Nivolumab plus rucaparib is active in patients with HRD-positive postchemotherapy or chemotherapy-naïve mCRPC, particularly those harboring BRCA1/2 mutations. Safety was as expected, with no new signals identified. Whether the addition of nivolumab incrementally improves outcomes versus rucaparib alone cannot be determined from this trial. Trial registration number: NCT03338790 .